2017
DOI: 10.1007/s40121-017-0171-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hepatitis C Treatment with Ombitasvir/Paritaprevir/R + Dasabuvir on Renal, Cardiovascular and Metabolic Extrahepatic Manifestations: A Post-Hoc Analysis of Phase 3 Clinical Trials

Abstract: IntroductionWe analyzed phase 3 trial data of ombitasvir/paritaprevir/ritonavir and dasabuvir (3D) ± ribavirin (RBV) in genotype 1 chronic hepatitis C patients to investigate the impact of 3D ± RBV on renal, cardiovascular and metabolic extrahepatic manifestations (EHMs), including persistency 52 weeks post treatment and differential impact by EHM disease severity.MethodsEstimated glomerular filtration rate (eGFR), fasting triglyceride and fasting glucose values from clinical trials were used to assess renal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 34 publications
1
26
0
1
Order By: Relevance
“…There is a wide literature supporting that HCV infection increases the subclinical and clinical risk of CV diseases [2][3][4][5][6][7][8][9][10][11] through multiple direct and indirect proatherogenic immune and inflammatory mechanisms, metabolic alterations (insulin resistance, diabetes) and a direct cardiovascular tropism of HCV [27]. Some studies evaluated the effect of clearance of HCV by DAAs on pro-atherosclerosis metabolic alterations [20,28,29]. An analysis of a large population of HCV patients treated with DAAs showed that those who achieved SVR had a significant improvement in some CV risk biomarkers [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a wide literature supporting that HCV infection increases the subclinical and clinical risk of CV diseases [2][3][4][5][6][7][8][9][10][11] through multiple direct and indirect proatherogenic immune and inflammatory mechanisms, metabolic alterations (insulin resistance, diabetes) and a direct cardiovascular tropism of HCV [27]. Some studies evaluated the effect of clearance of HCV by DAAs on pro-atherosclerosis metabolic alterations [20,28,29]. An analysis of a large population of HCV patients treated with DAAs showed that those who achieved SVR had a significant improvement in some CV risk biomarkers [28].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies evaluated the effect of clearance of HCV by DAAs on pro-atherosclerosis metabolic alterations [20,28,29]. An analysis of a large population of HCV patients treated with DAAs showed that those who achieved SVR had a significant improvement in some CV risk biomarkers [28]. A prospective study evaluated IR changes after SVR in patients treated with DAAs [20] demonstrated a normalization or reduction of IR levels in 76% of cases and a significant improvement CV: cardiovascular; OR: odds ratio; CI: confidence interval; BMI: body mass index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation could derive from the observation that viral clearance with DAAs determines a significant improvement of extrahepatic diseases such as cardiovasculopathies and nephropathies, regardless of the presence of DM. A recent American study [54] showed a significant improvement in extrahepatic manifestations accompanying C virus infection in patients with CHC cured after therapy with DAAs. The percentage of diabetics in this population was less than 10%.…”
Section: Do Daa-induced Glycemic Changes Determine a Significant Clinmentioning
confidence: 97%
“…HCV infection was associated with a nearly 30% increase of CVD and markedly reduced disability-adjusted life-years [1]. Treatment with novel DAAs was shown to reduce CVD events, which underscores the paramount role of timely HCV diagnosis and antiviral treatment [10].…”
mentioning
confidence: 96%